Aesthetics of Timbre in late Eighteenth-Century and Early Romantic German Scientific, Philosophical and Music-related Literature - Errington, Benjamin James (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of German, 2023)
Until recently timbre has generally been considered as first emerging as a Nineteenth and Twentieth-Century concept. This interdisciplinary thesis explores the existence of timbre as a concept during the period spanning circa 1760 to 1810, exploring definitions of timbre and other literary manifestations of timbre-understanding in German thought. Following a review of recent secondary literature and using a mixed-research methodology, the question of timbre-understanding in late Eighteenth-Century and Early Romantic German scientific, philosophical and music-related discourses is explored via five aesthetics-related access-points. These are, respectively, (1) organological, (2) acoustical, (3) physiological, (4) epistemological (post-Kantian) and (5) speculative meta-approaches. The last of these covers timbre-understanding in relation to the question of the origins of music and language. A considerable number of authors and texts is considered and the output of certain authors overlaps between several access-points, which only serves to show the rich diversity of the topic of timbre which appears in organological and musical treatises, works on acoustics, natural science, Naturphilosophie, physiology, neurology, musical-aesthetics, epistemology, theosophy, theology, works on the subject of language and works of fiction from the Early Romantic period. The authors discussed include Chladni, Herder, Hamann, Schubart, S?mmerring, Ritter, Kant, K?rner, Schiller, Schelling and Novalis. The division into these five access-points also reveals that timbre-understanding, which was surprisingly developed in some of the texts considered, ran parallel with Counter-Enlightenment approaches to aesthetics and significant trends of Romantic Science and (post-Kantian) philosophy that paved the way for the increasingly central place in music and aesthetic-acoustic theories that timbre was to achieve in the Twentieth-Century and beyond.
APPROVED
Keywords: musical aesthetics; intellectual history; German Romanticism.; Timbre; aesthetics